Social representations on family for graduates in social work: transformations in the formative process (Research, Society and Development, 2009)
Supported by current legislation and the theoretical-methodological apparatus of the profession, social workers represent a professional class that fights for equality and access to social rights, and has in families units of intervention in public projects and policies. Through this study, we sought to identify and analyze the Social Representations about family in the training course of future social workers. Semi-structured interviews were conducted on 30 subjects in different periods of the Social Work course, and the data were analyzed through Content Analysis in conjunction with the lexical analysis using the Iramuteq Software. It was verified that the students represent the Family in four classes: a) structure and concept; b) characteristics; c) personal experience; and d) intervention and guarantee of rights. The SR studied has two scopes, on the one hand the personal experiences and, on the other hand those of the professional formation, both undergoing changes during the course of Social Work. It should be noted that throughout the formative process the interviewees move their SRs about the object in question, due to their practices, stages, experiences in the disciplines and moments of discussion.